2017
DOI: 10.1093/jac/dkx270
|View full text |Cite
|
Sign up to set email alerts
|

Fitness cost constrains the spectrum of marR mutations in ciprofloxacin-resistant Escherichia coli

Abstract: ObjectivesTo determine whether the spectrum of mutations in marR in ciprofloxacin-resistant clinical isolates of Escherichia coli shows evidence of selection bias, either to reduce fitness costs, or to increase drug resistance. MarR is a repressor protein that regulates, via MarA, expression of the Mar regulon, including the multidrug efflux pump AcrAB-TolC.MethodsIsogenic strains carrying 36 different marR alleles identified in resistant clinical isolates, or selected for resistance in vitro, were constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 47 publications
2
41
0
Order By: Relevance
“…This process inevitably leads to the accumulation of inactivating mutations in the genes of the duplicated region that are not under positive selection. Gene-inactivating mutations (for example, frameshift, nonsense, deletion) occur with spontaneous rates of 10 −5 to 10 −6 per gene [46,47]. Recombination between repeat sequences that lie within the duplicated region (IS elements for example, or other repeat sequences) could lead to a loss of parts of a duplication, including a copy of an essential gene, at much higher rates.…”
Section: The Snap Hypothesismentioning
confidence: 99%
See 3 more Smart Citations
“…This process inevitably leads to the accumulation of inactivating mutations in the genes of the duplicated region that are not under positive selection. Gene-inactivating mutations (for example, frameshift, nonsense, deletion) occur with spontaneous rates of 10 −5 to 10 −6 per gene [46,47]. Recombination between repeat sequences that lie within the duplicated region (IS elements for example, or other repeat sequences) could lead to a loss of parts of a duplication, including a copy of an essential gene, at much higher rates.…”
Section: The Snap Hypothesismentioning
confidence: 99%
“…A minimal mathematical model of SNAP is presented in Fig 2. The spontaneous rates of duplication and mutational gene inactivation used in modelling are taken from published literature [30,46,47]. The only variable parameter in the model is the range of potential effects on relative fitness of duplications and mutations within duplicated regions.…”
Section: Mathematical Modelling Of Snapmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, AcrAB+, which overexpresses efflux pumps, was less evolvable and never achieved as high levels of resistance as the WT strain, suggesting that both having pumps and the ability to precisely control their expression together are important in the evolution of resistance. This reduced evolvability of AcrAB+ may be a result of the fitness burden of constitutive pump overexpression (25,46). In contrast, we found that under certain conditions the acrB strain evolved to survive on 40x MIC 0 .…”
Section: Discussionmentioning
confidence: 74%